Influence Style Leadership, Culture Organization and Climate Organization to Organizational Citizenship Behavior in The Company with Satisfaction Work as a Mediating Variable - Aripin Aripin; A.A Alit Merthayasa; Feri Hardiyanto; Amelia (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2024)
This research aimed to assess the impact of leadership style, organizational culture, and organizational climate on organizational citizenship behavior (OCB), utilizing job satisfaction as a mediating variable. The study encompassed the entire marketing department staff of PT X, totaling 212 employees. Structural Equations Modeling (SEM) through the LISREL Program was employed as the statistical method. The findings revealed that leadership style emerged as the most robust predictor, exerting the most substantial influence on organizational citizenship behavior, with job satisfaction acting as a mediating factor. This study contributes to validating the hypothesized relationships among leadership style, organizational culture, organizational climate, job satisfaction, and organizational citizenship behavior.